2020
DOI: 10.1186/s13046-020-01700-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural antisense transcripts in the biological hallmarks of cancer: powerful regulators hidden in the dark

Abstract: Natural antisense transcripts (NATs), which are transcribed from opposite strands of DNA with partial or complete overlap, affect multiple stages of gene expression, from epigenetic to post-translational modifications. NATs are dysregulated in various types of cancer, and an increasing number of studies focusing on NATs as pivotal regulators of the hallmarks of cancer and as promising candidates for cancer therapy are just beginning to unravel the mystery. Here, we summarize the existing knowledge on NATs to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 186 publications
(173 reference statements)
1
45
0
Order By: Relevance
“…In the ChiTaRS database, MYC was found to generate one SAS chimera, while EGFR can generate two, and TP53 can generate three such chimera. Several natural antisense transcripts (NATs) were identified for MYC ( 88 , 89 ), EGFR ( 90 , 91 ) and TP53 ( 92 , 93 ), which are involved in the antisense‐mediated regulation of these genes and play pivotal roles in cancer ( 94 ). Therefore, it is possible that trans-splicing could promote the fusion of the sense and antisense transcripts of the same gene and produce sense-antisense transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…In the ChiTaRS database, MYC was found to generate one SAS chimera, while EGFR can generate two, and TP53 can generate three such chimera. Several natural antisense transcripts (NATs) were identified for MYC ( 88 , 89 ), EGFR ( 90 , 91 ) and TP53 ( 92 , 93 ), which are involved in the antisense‐mediated regulation of these genes and play pivotal roles in cancer ( 94 ). Therefore, it is possible that trans-splicing could promote the fusion of the sense and antisense transcripts of the same gene and produce sense-antisense transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence has shown that many protein-coding mRNAs have natural antisense transcripts and that these non-coding RNAs account for most of the length of each mRNA. 21,22 Natural antisense transcript RNAs (NATs) are closely associated with the occurrence and development of cancer. For instance, NKX2-1-AS1 upregulates oncogene NKX2-1 and promotes the proliferation of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…This alternate isoform retains the IRES and has increased translational efficiency when compared to the spliced isoform without the IRES. Alterations in regulatory mechanisms resulting in the overexpression of ZEB2-AS have been associated with acute myeloid leukemia [97], bladder cancer [98] and other cancers [99].…”
Section: Examples Of Nats In Eukaryotic Cell Systemsmentioning
confidence: 99%